A Bibliometric Analysis of Epistemic Beliefs Research: Trends and Knowledge Structure in Education - Loso Judijanto (The Eastasouth Journal of Learning and Educations, 2026)
This study aims to provide a comprehensive bibliometric analysis of epistemic beliefs research in education by examining its development, intellectual structure, and emerging trends. Using a dataset of publications indexed in Scopus from 2010 to 2025, this study applies bibliometric techniques, including co-occurrence, overlay, and density visualization, to map the evolution of the field. The analysis was conducted using VOSviewer to identify key themes, influential topics, and relationships among research variables. The findings reveal that epistemic beliefs research is strongly centered on educational contexts, with dominant themes including learning, teaching, epistemology, and higher education. Over time, the field has evolved from focusing on pedagogical structures and curriculum design toward learner-centered constructs such as motivation, self-efficacy, and epistemic cognition. More recent trends indicate a growing emphasis on critical thinking, artificial intelligence, and digital learning environments, reflecting the increasing complexity of knowledge construction in contemporary education. The density analysis further highlights a mature research core complemented by emerging topics that offer significant opportunities for future investigation. Despite its growth, the field remains fragmented across disciplines, suggesting the need for greater theoretical integration and practical application. This study contributes to the literature by providing a systematic mapping of epistemic beliefs research and offering insights into its future directions, particularly in addressing challenges related to digital transformation and information evaluation in education.